Polityka międzynarodowa w sferze działań i postulatów Omida Nouripoura = Omid Nouripour's political demands and activities - Kruk, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article focuses on the political activity of Omid Nouripour - a German politician of Persian descent, member of the Green Party. He specializes in immigration and security politics and participates in German Bundestag's Committees for Human Rights, Humanitarian Aid and Foreign Politics and Security.
Keywords: dżihad; Niemcy; Zieloni; jihad; Germany; Greens